2022
DOI: 10.1109/tcds.2021.3115228
|View full text |Cite
|
Sign up to set email alerts
|

Conversational Affective Social Robots for Ageing and Dementia Support

Abstract: Socially assistive robots (SAR) hold significant potential to assist older adults and people with dementia in human engagement and clinical contexts by supporting mental health and independence at home. While SAR research has recently experienced prolific growth, long-term trust, clinical translation and patient benefit remain immature. Affective human-robot interactions are unresolved and the deployment of robots with conversational abilities is fundamental for robustness and humanrobot engagement. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 121 publications
(275 reference statements)
0
28
0
Order By: Relevance
“…There has been increasing interest in recent years in exploring how new developments in conversational AI and socially assistive robots can be applied to support active and healthy ageing. [3] presents a comprehensive state-of-the-art review in which several future research directions are identified, including: the need for unconstrained natural language processing and conversational strategies to enable robust and meaningful twoway conversations; the ability to interpret affective modalities in order to enhance user engagement and trust; and challenges in deployment of ensuring user adherence and data privacy. Looking at some individual relevant projects, [4] reports a month-long study of a virtual agent and robot that could interact with older adults in their homes through dialogue and gestures with the aim of providing companionship and reducing isolation.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been increasing interest in recent years in exploring how new developments in conversational AI and socially assistive robots can be applied to support active and healthy ageing. [3] presents a comprehensive state-of-the-art review in which several future research directions are identified, including: the need for unconstrained natural language processing and conversational strategies to enable robust and meaningful twoway conversations; the ability to interpret affective modalities in order to enhance user engagement and trust; and challenges in deployment of ensuring user adherence and data privacy. Looking at some individual relevant projects, [4] reports a month-long study of a virtual agent and robot that could interact with older adults in their homes through dialogue and gestures with the aim of providing companionship and reducing isolation.…”
Section: Related Workmentioning
confidence: 99%
“…The complete e-VITA platform is based on the Digital Enabler platform provided by the project partner Engineering (Italy) 3 . The platform is designed to include multiple devices and software components from across Europe and Japan that are based on different technologies and standards.…”
Section: Technologies and Architecture Of The Virtual Coachmentioning
confidence: 99%
“…[6]- [15]. Research has also considered cloud processing in such systems that could provide support back to the individual or supply their family and caregivers with information related to well-being, thus providing more advanced functions and services to support aging-in-place [14], [16], [26]- [28]. Many research projects have explored such possibilities where some projects focused on (1) daily cognitive evaluations through homebased sensing [6], [11], [15], [29], (2) detection of overnight wandering in Dementia patients using a multi-sensor system [8]- [10], (3) the challenges accompanied by cloud processing and data analytics in smart home systems [16], [26], [27], (4) the security and reliability aspects of smart home systems [14], (5) real-time location tracking in indoor environments using Wi-Fi and a wearable sensor [30], (6) monitoring of user activity and rate of activity using RF-ID technology [31], (7) deployment of in-home robots to provide human-level social engagement and support for elderly with dementia [28], and (8) determining electrodermal activity as means for emotion-sensing using a wearable Printed Circuit Board (PCB) [32].…”
Section: Supportive Smart Home Systemsmentioning
confidence: 99%
“…An integral part of supportive smart home systems is cloud processing. It could provide real-time support and feedback to individuals and their families by deploying algorithms in the cloud that analyze data (sensor measurements) sent from a supportive smart home system in real-time [5], [8], [9], [15], [28], [33]- [37]. In addition, cloud-recorded data can be used to perform analytics to determine an individual's overall health and well-being.…”
Section: Systemsmentioning
confidence: 99%
See 1 more Smart Citation